Ecological Significance of Laser Leveling of Lands. - A.M.Abdulloyev; A.B.Ochilov; A.B.To’xtamishov (Universitas Muhammadiyah Sidoarjo, 2022)
The economic efficiency of laser leveling of lands is that in Uzbekistan the cultivation of agricultural crops is based on irrigated agriculture, where 90-95% of the crop is grown. Caring and cultivation of crops is carried out by applying several agro-technical measures, the most important of which is land leveling. In agriculture, the main purpose of land leveling is to carry out irrigation and mechanized agro-technical measures while maintaining the slope of the field.